Use of Tocilizumab in Management of Post-Operative Myelomonocytic Leukemoid Reaction. (2020) - Melody, Megan; Butts, Emily; Menke, David; Landolfo, Kevin; Oken, Keith; Sher, Taimur; Khurana, Sharad
Abstract: Interleukin 6 receptor (IL6R) inhibitor, tocilizumab, has been effectively used in the treatment of cytokine release syndrome in patients receiving chimeric antigen receptor T-cell therapy. Here we present a patient with chronic myelomonocytic leukemia (CMML) who developed a steroid refractory, post-operative myelomonocytic leukemoid reaction (PO-MMLR), effectively treated with tocilizumab. Although, further studies are needed to validate the effectiveness of tocilizumab in management of PO-MMLR, this case serves to provide a new management approach in treatment of this rare but lethal syndrome with no standardized treatment options.